(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
During the last nine years of research and monitoring of rare plants populations in the vicinity of Vyshgorod, the town north of Kyiv (Ukraine), it has been shown that the population of Equisetum telmateia is stable, though it suffers from recreation activities (trampling, etc). Epipactis palustris populations mostly reflect changes of surrounding vegetation. Two orchids, Liparis loeselіi and Listera ovata, are persistently rare, but with a good age structure and with vegetative reproduction. Dactylorhiza incarnatа is more abundant; its age structure is good in all studied fragments of populations. These populations are especially important for saving the gene pool of the species in the territory affected by the sucking vortex of Kyiv fervent development. The localities of Orchis coriophora and Orchis palustris are very valuable. The abundance of Salvinia natans strongly fluctuates. Vyshgorod and its vicinity is an inestimable refuge for number of regionally rare species, which should be studied more profoundly. Our data represent an argument for (1) enlargement of the natural monument "Velykyj Hwosch", (2) creation of new natural reserves "Silskyj Yar" and "Gorianskyj Yar" in Vyshgorod gullies and (3) creation of the botanical natural monument “Orchidejna girka” on the bank of Dnieper.